Results of long-term biological monitoring of pacific salmons in the hatcheries of Kamchatsky Krai - Alexander V. Bugaev; Nadezhda A. Rastyagaeva; Natalya N. Romadenkova; Marina A. Kudzina; Denis A. Davidyuk; Tatyana V. Gavruseva; Elena A. Ustimenko; Elena V. Bochkova; Evgeny G. Pogodaev (Известия ТИНРО, 2015)
The following biological problems of the pacific salmons cultivation in Kamchatka are considered on the base of long-term monitoring data (2001-2013): 1) dynamics of cultivated salmons abundance in the water bodies of salmon hatcheries; 2) salmon otolith marking; 3) biological state of salmon juveniles and adults; 4) epizooty in hatcheries; 5) assessment of hatcheries effectiveness and prospects of salmon cultivation in Kamchatka. Four pacific salmon species are cultivated in Kamchatka: chum salmon (~ 60-70 %), sockeye salmon (~ 25-30 %), chinook salmon (~ 2-3 %), and coho salmon (~ 2-3 %). Their total annual release from Kamchatka hatcheries is estimated as approximately 36 million juveniles on average for the period 2001-2013. Mean contribution of chinook, sockeye and coho salmons cultivated in Kamchatka to the total release of these species from all Far-Eastern hatcheries is 100 %, 95 % and 35 %, respectively, but the contribution of chum salmon does not exceed 3-5 % of its total release. Total annual return of the salmons to Kamchatka hatcheries is about 38,000 on average, so the coefficients of return are usually < 1 % that means rather poor effectiveness of the hatcheries. The highest coefficient of return (2.1 %) is reached in Malkinsky hatchery that uses local geo-thermal water for rearing of salmon juveniles. To enhance the returns, illegal fishing (poaching) should be limited as much as possible and technologies of rearing have to be enhanced. Besides, the process of otoliths marking for cultivated juveniles in hatcheries has to be strictly controlled by technical standards for better evaluation of their contribution to commercial stocks. Promising ways of salmon fishery industry development in Kamchatka are ranching, supporting of wild salmon reproduction, and regulation of traditional fishery. All these measures should minimize effects of hatchery cultivation on structure of the stocks of pacific salmons. Health surveillance for hatchery-reared juveniles has to prevent and/or reduce their mortality in case of infectious, parasitical, alimentary and others diseases.